Little Paula [large type] - Andrews, V. C. (Virginia C.) (The Eden series, 2023)
"Faith Eden's brief foray into motherhood is marked by tragedy. Distraught that her baby was ripped away from her, she is determined to get little Paula back from the wealthy family who adopted her. Her brother, Trevor, is also anxious to get the baby back and will do anything necessary to do so. But when the dark truth comes to light, this twisted family will stop at nothing to keep outsiders out and secrets in -- no matter the cost."--